Introduction to a study of preferred colour rendering of light sources. (February 2015) - Schanda, J; Csuti, P; Szabó, F; Bhusal, P; Halonen, L
The European Union has financed a 3-year research project to establish optimal spectral power distributions of LED light sources for use in offices, commerce and homes. This paper summarizes the general questions relevant to colour preference investigations and introduces the investigations performed in the three laboratories that participated in the research. Subsequent papers will deal with details of the investigations and provide recommendations for optimum spectra in different indoor applications.